E-TEKNOLOGI : PENINGKATAN PRODUKSI HIDROPONIK INTEGRATED FARMING BERKELANJUTAN BAGI KETAHANAN PANGAN - Sulistyanto, Amin; Prasetya, Farid Adi; Suranto, Suranto (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
The Synergy Farmers Group in Kliwonan Village RT 16 Masaran Sragen, has potential in the agricultural sector, especially vegetable cultivation. There are 20 farmer members utilizing a 1500 meters garden, currently planted with: chili, spinach, eggplant, tomatoes; still planted in wet land. The garden farmer group aims to; (a) meet the need for organic vegetables by utilizing manure. (b) joint gardening efforts can run, working together, in resilience food. Problems: (1) Production aspects include: (a) the number of plant variants is still small, more plant variants are needed considering the land is quite large; (b) land utilization for increasing production capacity, product diversification and fulfillment of organic vegetables. (2) Management aspects include: (a) management of governance to meet the need for organic vegetables, (b) increasing the spirit of joint business, (c) utilization of products from, by and for members, (d) increasing community management through land utilization with hydroponic technology. Solutions with interactive participatory service methods, as well as transfer of technology, knowledge, skills, diffusion of science and technology and entrepreneurship capacity building are framed in e-technology to increase sustainable integrated farming hydroponic production for resilience food. Activity stages: preparation, implementation, monitoring and evaluation, results report and output report. Community service results: (a) increased production capacity, increased income, and production diversification, (b) strengthening entrepreneurial mentality, business management motivation, governance, and marketing.